Clinical profile of multisystem inflammatory syndrome in children associated with COVID-19 in a rural medical college - Khuntdar, Bidyut Kumar; Naik, Surjit; Roy, Arghya K.; Mohanta, Mahesh P.; Mandol, Sumon (International Journal of Contemporary Pediatrics, 2022)
Background: Multisystem inflammatory syndrome in children (MIS-C) is a newly recognised syndrome temporally associated with SARS CoV-2 infections. Methods: This was an observational both retrospective and prospective study in a rural medical college in eastern India. MIS‑C was diagnosed as per the criteria given by the WHO. Results: First case of MIS-C of the institute was found in November 2020, maximum cases were seen during the second wave. There were 66 cases. Mortality was 6%. All presented with fever. There was swelling of joints in 56.6% cases, gastrointestinal symptoms in 65%, respiratory distress in (43.9%) and shock was present in 12.1% of cases in this study. Co-morbidities were present only in four cases (6%). Conclusions: All cases of MIS-C had evidence of past infection with SARS CoV-2. There were relatively more cases of joint involvement and relatively less cases of shock in this study. The treatment using IVIG and methyl prednisolone was satisfactory. The 50% of the mortality was due to co-morbidities.